Ultra-thin meta-aramid fibrid as well as preparation method and application thereof

By performing precision coating and high-pressure hydraulic shock on the meta-aramid resin solution, the problem of uneven fiber thickness and morphology in the prior art was solved, and ultra-thin uniform film-shaped meta-aramid aramid precipitation fiber was prepared. , improves paper-forming performance, especially electrical strength, and meets application requirements in high-end fields.

CN119145077AActive Publication Date: 2024-12-17CHANGCHUN SANOFANG MATERIALS CO LTD

Patent Information

Application Number
CN202411461896.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-17
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The prior art cannot prepare ultra-thin uniform film-shaped mesoameric aramid precipitation fibers, resulting in different fiber thicknesses and irregular shapes, affecting paper-forming performance, especially poor electrical insulation performance, and difficult to meet the application requirements in high-end fields.

Method used

Precisely coated and applied to a flat substrate by polymerization, solidified in a solidification bath and crushed by high-pressure hydraulic impact. Ultra-thin meta-aramid fibers were collected and washed to obtain ultra-thin meta-aramid precipitation fibers to achieve fibers Accurate control of thickness and regularity of shape.

Benefits of technology

The prepared ultra-thin meta-aramid aramid fibers have uniform thickness and regular morphology, which improves the bonding degree of paper-forming fibers and paper uniformity, enhances the current barrier ability under the action of electric fields, and surpasses imported products to meet the needs of Application requirements in high-end fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145077A_ABST
    Figure CN119145077A_ABST
Patent Text Reader

Abstract

The invention provides an ultra-thin meta-aramid fibrid and a preparation method and application thereof, the preparation method comprises the following steps: (1) preparation of a meta-aramid resin solution: adding isophthaloyl dichloride and m-phenylenediamine into a solvent for polymerization reaction, neutralizing, filtering and diluting to obtain the meta-aramid resin solution; (2) preparation of meta-aramid fibrid: coating a substrate with the prepared meta-aramid resin solution to obtain an ultra-thin resin coating, allowing the ultra-thin resin coating to enter a coagulating bath along with the substrate to be coagulated and separated out to obtain an ultra-thin fiber layer, allowing the ultra-thin fiber layer to go out of the coagulating bath and then to be subjected to high-pressure hydraulic impact crushing, and then washing to obtain the meta-aramid fibrid. The ultra-thin meta-position aramid fiber fibrid is obtained. By adopting the preparation method provided by the invention, the ultra-thin meta-position aramid fibrid can be prepared, the thickness of the ultra-thin meta-position aramid fibrid is as low as 0.3-2 microns, the thickness and shape of the fibrid are regular and uniform, the membranous structure is rich, and the thickness size of the ultra-thin meta-position aramid fibrid can be accurately controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of synthetic fibers, specifically to the technical field of aramid fiber preparation, and relates to an ultra-thin meta-aramid fiber precipitate and a preparation method and application thereof, and in particular to an ultra-thin uniform film-like meta-aramid fiber precipitate and a preparation method and application thereof. Background Art

[0002] High-performance aramid paper has excellent mechanical strength, electrical insulation, high temperature resistance, flame retardancy, chemical corrosion resistance and other properties, and has become an important basic material for high-end fields such as rail transit, aerospace, national defense and military industry, and new energy. As one of the key raw materials for aramid paper, meta-aramid fiber precipitation has excellent flexibility, chemical stability, flame retardancy, and outstanding high temperature resistance and insulation properties. It plays a filling and bonding role in the composition structure of aramid paper, and usually accounts for more than 50% of aramid paper. Its structure and performance are crucial to paper sheet formation and product characteristics, and have a huge impact on the mechanical strength of aramid paper, especially the electrical insulation performance.

[0003] At present, the research on meta-aramid fibrid at home and abroad mainly focuses on the improvement of precipitation equipment and precipitation process, but there is a lack of research on the control of the thickness, morphology and uniformity of the fibrid and its impact on the paper properties. The meta-aramid fibrid prepared by the traditional process is to inject the meta-aramid resin solution into the coagulation bath or precipitating agent in the form of a thin stream, and the film-like or strip-like fibers are precipitated under the action of high-speed shearing. This process is completed in the precipitator.

[0004] CN1952226A discloses a meta-aramid fiber precipitation fibril and a preparation method thereof, wherein a meta-aramid amide stock solution and a certain proportion of precipitation solvent are transported to a precipitation device for mixing at a stable low temperature, the precipitation device is operated at a specified speed, the stock solution is solidified to form ultra-short fibers while being sheared, and the precipitation solvent is washed out and recycled by a common pulp washing device. The existing other manufacturing methods of first spinning and then cutting into ultra-short fibers are changed, no other polymer monomers need to be added during the stock solution preparation process, key precipitation equipment is used, and the fiber is directly formed under high-speed shearing, and no pulping and refining process and equipment are required. The process is simple and effective, the solvent is not highly corrosive, and the recycling is simple and convenient.

[0005] CN106245141A discloses a method for producing high-purity meta-aramid fibrids, comprising the steps of resin heating, precipitate cooling, resin precipitation, and water washing and separation. The resin heating step reduces the apparent viscosity of the system, increases fluidity, improves production efficiency, and reduces production costs. The calcium ion content in the obtained meta-aramid fibrids is below 20 ppm.

[0006] CN115110171A discloses a method for preparing aramid fibrids, comprising the following steps: (1) preparing a neutral aramid polymer solution; (2) preparing a precipitation stock solution: adding a solvent and a modifier to the neutral aramid polymer solution, and fully mixing and dispersing the obtained spinning stock solution; the modifier is at least one of polyethylene glycol and polyvinyl pyrrolidone; (3) preparing aramid fibrids: transporting the precipitation stock solution to a precipitation device, and after a non-solvent intersection diffusion pre-solidification treatment, forming a sheet-like fibrid under the action of a primary high-speed shear. The fibrid preparation method provided by the invention is simple to operate, convenient for industrial production, and can prepare fibrids with a unique fibrillated tow-like morphology and a larger specific surface area.

[0007] CN115787123A discloses a method for preparing meta-aramid fibrils with concentrated length distribution and high water retention value, comprising the following steps: (1) preparing a meta-aramid resin solution, wherein the polymer content of the aramid resin solution is 6% to 14%, the logarithmic viscosity is 1.5 to 1.8 dL / g, and the temperature is 40°C to 70°C; (2) injecting the meta-aramid resin solution and a precipitating agent into a precipitator, precipitating and cooling to form a crude fibrillation product, and the crude fibrillation product is subjected to pulping, delamination, and sieving to obtain a fibrillation slurry; (3) washing the fibrillation slurry to obtain meta-aramid fibrils with concentrated length distribution and high water retention value. The prepared fibrillation has high water retention value, good dispersibility, uniform film structure, and concentrated length distribution.

[0008] The above-mentioned prior arts are all prepared based on the traditional process route, that is, preparing precipitated fibers through the high-speed shearing action of a precipitator. This route cannot produce ultra-thin precipitated fibers, and the fiber morphology is irregular, the thickness is uneven and uncontrollable.

[0009] In addition, some existing technologies have also made innovations in process routes.

[0010] For example, CN115627556A discloses a method for preparing a high-conductivity meta-aramid fibrid resin, wherein m-phenylenediamine is dissolved in DMAc, isophthaloyl chloride, modified conductive graphite / DMAc suspension, and isophthaloyl chloride are added in sequence for reaction, and then LiOH powder / DMAc suspension is added, and the pH is adjusted to neutral or weakly acidic to obtain the obtained product. The method also discloses a method for preparing a high-conductivity meta-aramid fibrid, wherein the fibrid resin is formed by spray coagulation, and the fiber appearance is in the form of a sheet film and a fiber broom.

[0011] CN114717678A discloses a method for preparing spiral ribbon-shaped aramid fibrids for papermaking, belonging to the technical field of synthetic fiber manufacturing, and comprising the following steps: preparing aramid polymer; emulsifying the aramid polymer; preparing a precipitation solution; mixing the emulsified aramid polymer and the precipitation solution in a ball mill at a high speed according to a proportion; and washing the aramid fibrids to form aramid fibrids with rich hairiness and a wide spiral ribbon shape.

[0012] Although the above-mentioned prior art has made innovations in the process route, the prepared precipitated fibers still have problems such as uneven fiber thickness, different shapes, and few membrane structures. It is still impossible to produce ultra-thin membrane-like meta-aramid precipitated fibers with uniform thickness and regular shape.

[0013] In view of the fact that the meta-aramid fibrils prepared by the prior art have less membrane-like structures, large differences in fiber morphology, and an average fiber thickness of 3 to 8 μm, and their thickness and morphology are irregular and non-uniform, it is impossible to prepare ultra-thin fibrils, resulting in the fiber arrangement in the forming process being not regular and orderly, the fiber bonding degree of the finished paper being poor, and the uniformity of the paper being poor, the filling and bonding effect of the microscopic pores being insufficient, and the ability to hinder the passage of current when subjected to the electric field being weak, resulting in unsatisfactory product performance that is difficult to meet the application requirements of high-end fields. Therefore, how to provide an ultra-thin uniform membrane-like meta-aramid fibrils has become a technical problem that needs to be urgently solved in the preparation of high-performance aramid paper. Summary of the invention

[0014] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an ultra-thin meta-aramid fibrils and a preparation method and application thereof, and in particular to provide an ultra-thin uniform film-like meta-aramid fibrils and a preparation method and application thereof. The ultra-thin fibrils prepared by the preparation method provided by the present invention have controllable and uniform fiber thickness, regular morphology, and are rich in a large number of film-like structures. When the fibrils of the present invention are used to paper meta-aramid paper, the fiber arrangement during the forming process is regular and orderly, the fiber bonding degree and uniformity of the finished paper are good, the microscopic pores are fully filled and bonded, and the ability to hinder the passage of current when subjected to an electric field is strong. The obtained product has excellent comprehensive performance, and indicators such as electrical strength exceed imported products, which can meet the application requirements of high-end fields and realize domestic substitution.

[0015] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0016] In a first aspect, the present invention provides a method for preparing ultra-thin meta-aramid fibrids, the preparation method comprising the following steps:

[0017] (1) Preparation of meta-aramid resin solution: adding isophthaloyl chloride and meta-phenylenediamine into a solvent for polymerization reaction, and then neutralizing, filtering and diluting to obtain a meta-aramid resin solution;

[0018] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a flat substrate to obtain an ultra-thin resin coating. The ultra-thin resin coating enters a coagulation bath along with the substrate to coagulate and precipitate to obtain an ultra-thin fiber layer. After the ultra-thin fiber layer comes out of the coagulation bath, it is crushed by high-pressure hydraulic impact, collected, and then fully washed to obtain the ultra-thin meta-aramid fibrids.

[0019] The present invention coats a meta-aramid resin solution prepared by polymerization on a flat substrate through precision coating, and the obtained ultra-thin resin coating enters a coagulation bath along with the substrate, and is coagulated and precipitated through a phase transition method to obtain an ultra-thin fiber layer, and then the precipitated ultra-thin fiber layer is uniformly crushed by high-pressure hydraulic impact, and after being collected and fully washed, an ultra-thin meta-aramid fibrid is obtained, and the fibrid has a uniform film structure. The aramid paper made by using the fibrid of the present invention has more excellent comprehensive performance.

[0020] Preferably, the molar ratio of isophthaloyl chloride to metaphenylenediamine in step (1) is (0.95-1.05):1, for example, 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, etc.

[0021] Preferably, the solvent in step (1) comprises N,N-dimethylformamide (DMF) and / or N,N-dimethylacetamide (DMAC).

[0022] Preferably, the solvent used for the dilution in step (1) comprises N,N-dimethylformamide and / or N,N-dimethylacetamide.

[0023] Preferably, the solvent used for the dilution in step (1) is the same solvent as the solvent used for the polymerization reaction.

[0024] Preferably, the concentration of the meta-aramid resin solution in step (1) is 5 to 15 wt.%, for example, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, etc.

[0025] Preferably, the coating in step (2) is precision coating, including any one of micro-concave coating, slit extrusion coating, and multi-roller transfer coating.

[0026] Preferably, the substrate in step (2) is a metal coil or a plastic film coil.

[0027] Preferably, the metal coil comprises copper foil or aluminum foil.

[0028] Preferably, the plastic film roll includes any one of a polyethylene film roll, a polypropylene film roll, a polyester film roll, a polyimide film roll, and a polytetrafluoroethylene film roll.

[0029] Preferably, the thickness of the substrate is 0.05-0.35 mm, for example, 0.05 mm, 0.08 mm, 0.1 mm, 0.13 mm, 0.15 mm, 0.18 mm, 0.2 mm, 0.23 mm, 0.25 mm, 0.28 mm, 0.3 mm, 0.32 mm, 0.34 mm, 0.35 mm, etc., and the substrate can be recycled.

[0030] Preferably, the thickness of the ultra-thin resin coating is 0.5-3 μm, for example, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, etc.

[0031] Preferably, the coagulation bath comprises an aqueous solution of N,N-dimethylformamide (DMF) and / or N,N-dimethylacetamide (DMAC) with a concentration of 20-50 wt.%, for example 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, etc.

[0032] Preferably, the high-pressure hydraulic impact crushing includes two-stage high-pressure spraying, wherein the pressure of the first-stage high-pressure spraying is 300-3000 kPa (for example, 300 kPa, 500 kPa, 800 kPa, 1000 kPa, 1200 kPa, 1400 kPa, 1600 kPa, 1800 kPa, 2000 kPa, 2200 kPa, 2400 kPa, 2600 kPa, 2800 kPa, 3000 kPa, etc.), and the pressure of the second-stage high-pressure spraying is 200-3000 kPa (for example, 300 kPa, 500 kPa, 800 kPa, 1000 kPa, 1200 kPa, 1400 kPa, 1600 kPa, 1800 kPa, 2000 kPa, 2200 kPa, 2400 kPa, 2600 kPa, 2800 kPa, 3000 kPa, etc.). The pressure is 500-4000kPa (for example, 500kPa, 800kPa, 1000kPa, 1200kPa, 1400kPa, 1600kPa, 1800kPa, 2000kPa, 2200kPa, 2400kPa, 2600kPa, 2800kPa, 3000kPa, 3200kPa, 3400kPa, 3600kPa, 3800kPa, 4000kPa, etc.), and the two-stage spraying is staggered.

[0033] Preferably, the high pressure spray comprises a needle spray.

[0034] That is, the high-pressure hydraulic impact crushing of the present invention includes two-stage high-pressure needle-shaped spraying, and the needle shapes of the two-stage spraying are staggered.

[0035] Preferably, the ultra-thin meta-aramid fibrid has a thickness of 0.3 to 2 μm, such as 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, etc., and a dryness of 5 to 20 wt.%, such as 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, etc. wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, etc., the initial beating degree is 40-60°SR, for example, 40°SR, 42°SR, 44°SR, 46°SR, 48°SR, 50°SR, 52°SR, 54°SR, 56°SR, 58°SR, 60°SR, etc., the beating degree after 120,000 revolutions of the standard deagulator is 65-90°SR, for example, 65°SR, 68°SR, 70°SR, 72°SR, 74°SR, 76°SR, 78°SR, 80°SR, 82°SR, 84°SR, 86°SR, 88°SR, 90°SR, etc.

[0036] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0037] (1) Preparation of meta-aramid resin solution: adding isophthaloyl chloride and meta-phenylenediamine into a solvent for polymerization reaction, and obtaining a meta-aramid resin solution with a concentration of 5 to 15 wt.% after neutralization, filtration and dilution;

[0038] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a substrate by micro-concave coating, slit extrusion coating or multi-roll transfer coating to obtain an ultra-thin resin coating with a thickness of 0.5 to 3 μm, and the ultra-thin resin coating enters an aqueous solution of N,N-dimethylformamide and / or N,N-dimethylacetamide with a concentration of 20 to 50 wt.% along with the substrate to coagulate and precipitate to obtain an ultra-thin fiber layer, and the ultra-thin fiber layer is subjected to two-stage high-pressure spraying after exiting the coagulation bath, and then washed to obtain the ultra-thin meta-aramid fibrids;

[0039] Among them, the pressure of the first-stage high-pressure spraying is 300-3000 kPa, the pressure of the second-stage high-pressure spraying is 500-4000 kPa, and the two-stage high-pressure spraying is staggered.

[0040] In a second aspect, the present invention provides an ultra-thin meta-aramid fibrid, wherein the ultra-thin meta-aramid fibrid is prepared by the preparation method described in the first aspect.

[0041] In a third aspect, the present invention provides a use of the ultra-thin meta-aramid fibrid as described in the second aspect in aramid paper.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The preparation method provided by the present invention can be used to prepare ultra-thin meta-aramid fibrids with a thickness as low as 0.3 to 2 μm. The thickness and morphology of the fibrids are regular and uniform, the membrane structure is rich, and the thickness size can be precisely controlled.

[0044] (2) The present invention prepares meta-aramid fibrils by a phase transition method, without using traditional equipment such as a precipitator. The equipment investment is small, the operation is convenient, the production efficiency is high, the auxiliary substrate can be reused, and continuous large-scale production can be achieved, which has a great cost advantage.

[0045] (3) The precipitated fibers prepared by the present invention are used to prepare aramid paper, which can effectively improve the regularity of fiber arrangement during the forming process, improve the fiber bonding degree and paper uniformity of the finished paper, fully fill and bond the microscopic pores, and increase the density of the paper sheet. The tensile strength, electrical strength, air permeability and other properties of the prepared aramid paper are significantly improved, surpassing the level of imported products, among which the electrical strength and other indicators exceed the imported products by more than 20%.

[0046] (4) The preparation concept of the ultra-thin uniform film-like meta-aramid fiber precipitate provided by the present invention can also be extended to products such as para-aramid (PPTA), polysulfone (PSA), and polyoxadiazole (POD). BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a process flow chart for preparing ultra-thin meta-aramid fibrid provided in an embodiment of the present invention.

[0048] Figure 2 This is a schematic diagram of the structure of an apparatus used to prepare ultra-thin meta-aramid fibrids according to an embodiment of the present invention;

[0049] Among them, 1-substrate unwinding section, 2-coating device, 3-coagulation bath, 4-coagulation bath, 5-coating support back roller, 6-first-level high-pressure spray, 7-second-level high-pressure spray, 8-fiber collection tank, 9-substrate winding section.

[0050] Figure 3 This is the SEM image of the ultra-thin meta-aramid fiber prepared in Example 1.

[0051] Figure 4 This is the SEM image of the ultra-thin meta-aramid fiber prepared in Example 2.

[0052] Figure 5This is the SEM image of the meta-aramid fiber prepared in Comparative Example 1.

[0053] Figure 6 This is a surface SEM image of the aramid paper made from the ultra-thin meta-aramid fibrid prepared in Example 1 before hot pressing.

[0054] Figure 7 This is a cross-sectional SEM image of the aramid paper made from the ultra-thin meta-aramid fibrid prepared in Example 1 before hot pressing.

[0055] Figure 8 This is a surface SEM image of the aramid paper made from the meta-aramid fibrillation prepared in Comparative Example 1 before hot pressing.

[0056] Fig. 9 This is a cross-sectional SEM image of the aramid paper made from the meta-aramid fibrillation prepared in Comparative Example 1 before hot pressing.

[0057] Fig.10 This is a surface SEM image of the aramid paper made from the ultra-thin meta-aramid fibrid prepared in Example 1 after hot pressing.

[0058] Fig.11 This is a cross-sectional SEM image of the aramid paper made from the ultra-thin meta-aramid fibrid prepared in Example 1 after hot pressing.

[0059] Fig.12 This is a surface SEM image of the aramid paper made from the meta-aramid fibrillation prepared in Comparative Example 1 after hot pressing.

[0060] Fig.13 This is a cross-sectional SEM image of the aramid paper made from the meta-aramid fibrillation prepared in Comparative Example 1 after hot pressing. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] In this embodiment, an ultra-thin meta-aramid fiber is provided, and a preparation method thereof comprises the following steps:

[0064] (1) Preparation of meta-aramid resin solution: isophthaloyl chloride and meta-phenylenediamine (the molar ratio of the two is 0.95:1) are added to N,N-dimethylformamide (DMF) for polymerization reaction, and after neutralization, filtration and dilution (the dilution solvent is DMF), an 8 wt.% meta-aramid resin solution is obtained, and its logarithmic viscosity is 1.6 dL / g;

[0065] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a flat copper foil by micro-dimpled coating. The copper foil has a thickness of 0.05 mm and the resin coating has a thickness of 0.5 μm. The resin coating enters a 30 wt.% N,N-dimethylformamide (DMF) aqueous solution with the copper foil to coagulate and precipitate to obtain a fiber layer. The fiber layer is taken out of the coagulation bath with the copper foil substrate and is uniformly crushed by two-stage high-pressure spray impact. The first-stage needle-shaped spray pressure is 1000 kPa and the second-stage needle-shaped spray pressure is 1500 kPa. The two-stage spray is staggered. The fibers are collected in a fiber collection pool and then washed thoroughly to obtain ultra-thin uniform film-like meta-aramid fibrids. The thickness of the fibers is 0.3 μm, the dryness is 8 wt.%, the initial beating degree is 58°SR, and the beating degree is 86°SR after being deflagrated by a standard deflagrator for 120,000 revolutions.

[0066] Example 2

[0067] In this embodiment, an ultra-thin meta-aramid fiber is provided, and a preparation method thereof comprises the following steps:

[0068] (1) Preparation of meta-aramid resin solution: isophthaloyl chloride and meta-phenylenediamine (the molar ratio of the two is 1.05:1) are added to N,N-dimethylacetamide (DMAC) for polymerization reaction, and after neutralization, filtration and dilution (the dilution solvent is DMAC), a 15 wt.% meta-aramid resin solution is obtained, and its logarithmic viscosity is 1.8 dL / g;

[0069] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a flat polyester film by slit extrusion coating. The thickness of the polyester film is 0.35 mm and the thickness of the resin coating is 3 μm. The resin coating enters a 20 wt.% N,N-dimethylacetamide (DMAC) aqueous solution with the polyester film to coagulate and precipitate to obtain a fiber layer. The fiber layer is discharged from the coagulation bath with the polyester film substrate and is uniformly crushed by two-stage high-pressure spray impact. The first-stage needle spray pressure is 3000 kPa and the second-stage needle spray pressure is 3500 kPa. The two-stage spray is staggered. The fibers are collected in a fiber collection pool and then washed thoroughly to obtain ultra-thin uniform film-like meta-aramid fibrids. The thickness of the fibers is 2 μm, the dryness is 15 wt.%, the initial beating degree is 45°SR, and the beating degree is 72°SR after being deflagrated by a standard deflagrator for 120,000 revolutions.

[0070] Example 3

[0071] In this embodiment, an ultra-thin meta-aramid fiber is provided, and a preparation method thereof comprises the following steps:

[0072] (1) Preparation of meta-aramid resin solution: isophthaloyl chloride and meta-phenylenediamine (the molar ratio of the two is 1:1) are added to N,N-dimethylacetamide (DMAC) for polymerization reaction, and after neutralization, filtration and dilution (the dilution solvent is DMAC), a 10 wt.% meta-aramid resin solution is obtained, and its logarithmic viscosity is 1.7 dL / g;

[0073] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a flat polypropylene film by multi-roll transfer coating. The thickness of the polypropylene film is 0.15 mm, and the thickness of the resin coating is 2 μm. The resin coating enters into a 40 wt.% N,N-dimethylacetamide (DMAC) aqueous solution with the polypropylene film to coagulate and precipitate to obtain a fiber layer. The fiber layer is discharged from the coagulation bath with the polypropylene film substrate and is uniformly crushed by two-stage high-pressure spray impact. The first-stage needle spray pressure is 2000 kPa, and the second-stage needle spray pressure is 3000 kPa. The two-stage spray is staggered. After the fibers are collected in a fiber collection pool, they are fully washed to obtain ultra-thin uniform film-like meta-aramid fibrids. The thickness of the fibers is 1.4 μm, the dryness is 12 wt.%, the initial beating degree is 51°SR, and the beating degree is 79°SR after being deflaked by a standard deflaker for 120,000 revolutions.

[0074] Example 4

[0075] In this embodiment, an ultra-thin meta-aramid fiber is provided, and a preparation method thereof comprises the following steps:

[0076] (1) Preparation of meta-aramid resin solution: isophthaloyl chloride and meta-phenylenediamine (the molar ratio of the two is 1:1) are added to N,N-dimethylformamide (DMF) for polymerization reaction, and after neutralization, filtration, and dilution (the dilution solvent is DMF), a 5 wt.% meta-aramid resin solution is obtained, and its logarithmic viscosity is 1.7 dL / g;

[0077] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a flat copper foil by micro-dimpled coating. The copper foil has a thickness of 0.05 mm and the resin coating has a thickness of 0.8 μm. The resin coating enters a 50 wt.% N,N-dimethylformamide (DMF) aqueous solution along with the copper foil to coagulate and precipitate to obtain a fiber layer. The fiber layer is taken out of the coagulation bath along with the copper foil substrate and is uniformly crushed by two-stage high-pressure spray impact. The first-stage needle spray pressure is 300 kPa and the second-stage needle spray pressure is 500 kPa. The two-stage spray is staggered. The fibers are collected in a fiber collection pool and then washed thoroughly to obtain ultra-thin uniform film-like meta-aramid fibrids. The thickness of the fibers is 0.4 μm, the dryness is 10 wt.%, the initial beating degree is 55°SR, and the beating degree is 84°SR after being defibrated by a standard defibrator for 120,000 revolutions.

[0078] Comparative Example 1

[0079] In this comparative example, a meta-aramid fiber is provided, and a preparation method thereof comprises the following steps:

[0080] (1) Preparation of meta-aramid resin solution: isophthaloyl chloride and meta-phenylenediamine (the molar ratio of the two is 0.95:1) are added to N,N-dimethylformamide (DMF) for polymerization reaction, and after neutralization, filtration and dilution (the dilution solvent is DMF), an 8 wt.% meta-aramid resin solution is obtained, and its logarithmic viscosity is 1.6 dL / g;

[0081] (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution and 30 wt.% N,N-dimethylformamide (DMF) aqueous solution (i.e., precipitating agent) were injected into a high-speed rotating disc precipitator at a volume ratio of 1:16. The flocculated fibers were continuously collected and washed thoroughly to obtain meta-aramid fibrids with an average thickness of 6 μm, a dryness of 20 wt.%, an initial beating degree of 35°SR, and a beating degree of 58°SR after being deflocculanted in a standard deflagrator for 120,000 revolutions.

[0082] Comparative Example 2

[0083] The only difference between this comparative example and Example 1 is that in step (2), the fiber layer is only subjected to one-stage high-pressure spray impact crushing after exiting the coagulation bath along with the copper foil substrate, and the needle-shaped spray pressure is 1000 kPa.

[0084] The process flow chart of the preparation of ultra-thin meta-aramid fiber provided by the embodiment of the present invention is as follows: Figure 1 As shown, the schematic diagram of the device structure used is as follows Figure 2 shown.

[0085] The SEM image of the ultra-thin meta-aramid fiber prepared in Example 1 of the present invention is as follows: Figure 3 As shown, the SEM image of the ultra-thin meta-aramid fiber prepared in Example 2 is as follows Figure 4 As shown, it can be seen that the meta-aramid fibrid provided by the embodiment of the present invention has a uniform film-like structure.

[0086] The SEM image of the meta-aramid fiber precipitated obtained in Comparative Example 1 is as follows: Figure 5 As shown, it can be seen that the meta-aramid fibrils provided in Comparative Example 1 have irregular morphology and uneven thickness. This is because Comparative Example 1 adopts a traditional preparation route, i.e., preparing fibrils through the high-speed shearing action of a precipitator, and ultra-thin fibrils cannot be prepared.

[0087] Preparation of Meta-aramid Paper

[0088] The prepared fibrids in the examples and comparative examples were respectively mixed with short-cut fibers (2D, 6 mm) at a mass ratio of 55:45 to produce a papermaking machine with a basis weight of 40 g / m 2 The meta-aramid paper is sampled and tested for performance after hot pressing. The test method is as follows:

[0089] (1) Thickness: Tested in accordance with GB / T 451.3-2002 “Determination of thickness of paper and paperboard”;

[0090] (2) Quantitative determination: Tested in accordance with GB / T 451.2-2023 “Paper and paperboard - Part 2: Determination of quantitative determination”;

[0091] (3) Tensile strength and elongation at break: tested in accordance with GB / T 20629.2-2013 “Non-cellulose paper for electrical use Part 2: Test methods”;

[0092] (4) Electrical strength: Tested in accordance with GB / T 1408.1-2016 "Electrical strength test methods for insulating materials - Part 1: Tests at power frequency";

[0093] (5) Air permeability: Tested according to the Schober method in GB / T 458-2008 “Determination of air permeability of paper and paperboard”.

[0094] The performance test results are shown in Table 1.

[0095] Table 1

[0096]

[0097] It can be seen from the data in the above table that the aramid paper made from the fibrillation prepared by the present invention has excellent tensile strength (MD: 4.04-4.15 kN / m; CD: 2.05-2.25 kN / m), elongation at break (MD: 6.9%-7.6%; CD: 6.3%-6.8%), electrical strength (21.9-22.7 kV / mm) and air permeability and barrier properties, especially the electrical strength and other properties exceed the imported samples by more than 20%.

[0098] The surface SEM images and cross-sectional SEM images of the aramid paper made of the ultra-thin meta-aramid fibrid prepared in Example 1 of the present invention before hot pressing are shown in FIG. Figure 6 and Figure 7 The surface SEM images and cross-sectional SEM images of the aramid paper made of meta-aramid fiber prepared in Comparative Example 1 before hot pressing are shown in FIG. Figure 8 and Fig. 9 shown.

[0099] The surface SEM images and cross-sectional SEM images of the aramid paper made of the ultra-thin meta-aramid fibrid prepared in Example 1 of the present invention after hot pressing are shown in FIG. Fig.10 and Fig.11 The surface SEM images and cross-sectional SEM images of the aramid paper made of meta-aramid fiber prepared in Comparative Example 1 after hot pressing are shown in FIG. Fig.12 and Fig.13 shown.

[0100] from Figure 6-Figure 13 It can be seen that compared with Comparative Example 1, when the precipitated fibers prepared in Example 1 are used to paper meta-aramid paper, the fiber arrangement during the forming process is regular and orderly, the fiber bonding degree and paper uniformity of the finished paper are good, and the paper sheets are denser.

[0101] In summary, the ultra-thin precipitated fibers prepared by the preparation method provided by the present invention have controllable and uniform fiber thickness, regular morphology, and are rich in a large number of membrane structures. When the precipitated fibers of the present invention are used to make meta-aramid paper, the fiber arrangement during the forming process is regular and orderly, the fiber bonding degree and paper uniformity of the finished paper are good, and the ability to hinder the passage of current when subjected to an electric field is strong. The obtained product has excellent comprehensive performance, and indicators such as electrical strength exceed imported products, which can meet the application requirements of high-end fields such as aerospace, national defense and military industry, rail transportation, and new energy, and realize domestic substitution.

[0102] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the ultra-thin meta-aramid fiber analysis and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing ultra-thin meta-aramid fiber precipitation, It is characterized in that The preparation method comprises the following steps: (1) Preparation of meta-aramid resin solution: adding isophthaloyl chloride and meta-phenylenediamine into a solvent for polymerization reaction, and then neutralizing, filtering and diluting to obtain a meta-aramid resin solution; (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a substrate to obtain an ultra-thin resin coating, and the ultra-thin resin coating enters a coagulation bath along with the substrate to coagulate and precipitate to obtain an ultra-thin fiber layer, and the ultra-thin fiber layer is crushed by high-pressure hydraulic impact after exiting the coagulation bath, and then washed to obtain the ultra-thin meta-aramid fibrids.

2. The preparation method according to claim 1, It is characterized in that The molar ratio of isophthaloyl chloride to m-phenylenediamine in step (1) is (0.95-1.05):1; Preferably, the solvent in step (1) comprises N,N-dimethylformamide and / or N,N-dimethylacetamide.

3. The preparation method according to claim 1 or 2, It is characterized in that The solvent used for the dilution in step (1) includes N,N-dimethylformamide and / or N,N-dimethylacetamide; Preferably, the concentration of the meta-aramid resin solution in step (1) is 5 to 15 wt.%.

4. The preparation method according to any one of claims 1 to 3, It is characterized in that The coating in step (2) includes any one of micro-concave coating, slit extrusion coating, and multi-roller transfer coating; Preferably, the substrate in step (2) is a metal coil or a plastic film coil; Preferably, the metal coil comprises copper foil or aluminum foil; Preferably, the plastic film coil includes any one of a polyethylene film coil, a polypropylene film coil, a polyester film coil, a polyimide film coil, and a polytetrafluoroethylene film coil; Preferably, the thickness of the substrate is 0.05-0.35 mm.

5. The preparation method according to any one of claims 1 to 4, It is characterized in that The thickness of the ultra-thin resin coating is 0.5-3 μm.

6. The preparation method according to any one of claims 1 to 5, It is characterized in that The coagulation bath comprises an aqueous solution of N,N-dimethylformamide and / or N,N-dimethylacetamide, with a concentration of 20 to 50 wt.%; Preferably, the high-pressure hydraulic impact crushing includes two-stage high-pressure spraying, wherein the pressure of the first-stage high-pressure spraying is 300-3000 kPa, the pressure of the second-stage high-pressure spraying is 500-4000 kPa, and the two-stage spraying is staggered; Preferably, the high pressure spray comprises a needle spray.

7. The preparation method according to any one of claims 1 to 6, It is characterized in that The ultra-thin meta-aramid fiber has a thickness of 0.3-2 μm, a dryness of 5-20 wt.%, an initial beating degree of 40-60° SR, and a beating degree of 65-90° SR after being deflated by a standard deflagrator for 120,000 revolutions.

8. A preparation method as claimed in any one of claims 1 to 7, It is characterized in that The preparation method comprises the following steps: (1) Preparation of meta-aramid resin solution: adding isophthaloyl chloride and meta-phenylenediamine into a solvent for polymerization reaction, and obtaining a meta-aramid resin solution with a concentration of 5 to 15 wt.% after neutralization, filtration and dilution; (2) Preparation of meta-aramid fibrids: The prepared meta-aramid resin solution is coated on a substrate by micro-concave coating, slit extrusion coating or multi-roll transfer coating to obtain an ultra-thin resin coating with a thickness of 0.5 to 3 μm, and the ultra-thin resin coating enters an aqueous solution of N,N-dimethylformamide and / or N,N-dimethylacetamide with a concentration of 20 to 50 wt.% along with the substrate to coagulate and precipitate to obtain an ultra-thin fiber layer, and the ultra-thin fiber layer is subjected to two-stage high-pressure spraying after exiting the coagulation bath, and then washed to obtain the ultra-thin meta-aramid fibrids; Among them, the pressure of the first-stage high-pressure spraying is 300-3000 kPa, the pressure of the second-stage high-pressure spraying is 500-4000 kPa, and the two-stage high-pressure spraying is staggered.

9. An ultra-thin meta-aramid fiber precipitation, It is characterized in that The ultra-thin meta-aramid fibrid is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ultra-thin meta-aramid fibrid according to claim 9 in aramid paper.

Citation Information

Patent Citations

  • Production method of high-purity meta-position aramid precipitation fibers

    CN106245141A

  • Preparation method of spiral ribbon-shaped aramid fibrid for papermaking

    CN114717678A

  • High-conductivity meta-aramid fibrid resin and preparation method of fibrid thereof

    CN115627556A

  • Meta-aramid fibre fibrid and its making method

    CN1952226A

  • Preparation method of meta-aramid paper

    CN104343041A

Cited By

  • Bio-based aramid fibrid as well as preparation method and application thereof

    CN121046973A

  • Bio-based aramid fibrids, methods of making, and applications thereof

    CN121046973B